A dual-route concept of persuasive user interface (UI) design - Ibrahim, Nurulhuda; Shiratuddin, Mohd Fairuz; Kok, Wai Wong (2013)
As current trends are moving towards designing for persuasion, designing for functionality and usability of a website is no longer sufficient. This paper identifies the factors of persuasion and their potential adaptation in UI design. The conceptual framework proposed and discussed in this paper refers to the Elaboration Likelihood Model (ELM). The ELM is used to identify and distinguish the design cues for the central route and peripheral route. This paper also identifies web design qualities that may improve the persuasiveness and likelihood of a website. The factors of persuasion identified in this paper; namely relationship, emotion, credibility, and logic; will then be tested using a repeated-measures technique of experimental design to verify their effectiveness in influencing users to stay and make further decision at a website.